All Days 1992
DOI: 10.2118/24642-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Foam Field Verification Pilot Test at EVGSAU: Phase II—Foam Injection Design and Operating Plan

Abstract: SPE Members Abstract The East Vacuum Grayburg San Andres Unit (EVGSAU) operated by Phillips Petroleum, is the site selected for a comprehensive evaluation of the use of foam for improving the sweep efficiency of a CO2 flood. The four-year project is jointly funded by the EVGSAU Working Interest Owners (WIO), the U.S. Department of Energy (DOE), and the State of New Mexico. The Petroleum Recovery Research Center (PRRC), a division of the New Mexico Institute o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…This test, a four-year project started late 1989 andjointly funded by the US DOE, the state of New Mexico and the field owners, has been well documented [20][21][22][23][24][25].…”
Section: East Vacuummentioning
confidence: 99%
See 1 more Smart Citation
“…This test, a four-year project started late 1989 andjointly funded by the US DOE, the state of New Mexico and the field owners, has been well documented [20][21][22][23][24][25].…”
Section: East Vacuummentioning
confidence: 99%
“…The objective of this test is to divert injected CO 2 from highpermeability zones and reduce breakthrough at the producers. Only near-well effects were expected due to surfactant adsorption [21], despite injection of a sacrificial slug. Rapid foamer solution slugs alternating with gas caused an increase in injection pressure, showing foain generation.…”
Section: East Vacuummentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) foams in porous media with aqueous soluble surfactants have been widely studied in connection with their application in enhanced oil recovery (EOR) (Lee and Heller 1988;Du et al 2007). These experimental and theoretical studies have contributed to the success of several field foam applications (Patzek 1996), especially for carbonate reservoirs (Hoefner et al 1995;Stevens 1995). Unfortunately, field experiences have shown that conventional foams with only aqueous soluble surfactants have some important limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Shan, et al [1] given an optimal foam-injection strategy in homogeneous reservoirs with a variety of foam models by using simulation. Stevens, et al [2] presented an overview of the operating plan for CO 2 foam injection and the details of the CO 2 foam injection schedule and design criteria in the East Vacuum Grayburg San Andres Unit. Hou, et al [3] compared three main injection modes, including co-injection of gas and solution, alternative injection of gas and solution, and direct injection of foam and pointed that the direct injection of foam was the most effective mode and the alternative injection of gas and solution is the poorest.…”
Section: Introductionmentioning
confidence: 99%